Implementation of Sanitation and Environmental Health As a Prevention of Tuberculosis Disease in Correctional Institute Class II B Mojokerto - Muhamad Hilmi Rahman Alauddin (Department of Guidance and Counseling, FIP, Undiksha, 2020)
This research focuses on the role of the BPJS health in implementing sanitation and environmental health programs as a prevention of Tuberculosis in correctional institute Class II B Mojokerto. The method used is descriptive by presenting a description of the state of the implementation of health services in detail based on the facts that can be interpreted to conclude The results of research showed that the environmental health program that was running less optimally and the absence of a special program to prevent tuberculosis. The tuberculosis prevention program is carried out according to the PPI TB procedure but is not optimal because there are many facilitative and administrative deficiencies